Avaliação dos limites de automação do projeto de alvenaria a partir do Método Building Object Behavior (BOB) - Pinheiro, Levi Teixeira (2015)
This research comes to inquiry ways of automating the masonry design in computer systems. Soon aims to develop applicable diagrams in BIM platforms, enabling automatic reordering of paging walls following the inclusion of new objects or shifting objects already inserted. Because of the complexity and diversity of types and existing architectural details, the BIM platforms do not always meet all the demands of users. Thus, we present customization possibilities, such as creating new objects or new tools that improve the design process. Thus, in the national and international levels is observed the production design automation techniques applied in different construction systems, whether armed or rationalized masonry concrete. Among the differences between national and international productions stands out the method used. In Brazil is the use of various methods based on the grammar of form and parametric modeling, besides the fact of the productions have been performed in universities and in different periods. In the international context there is the development and application of building object behavior method (BOB) description and notation method, developed for a consortium of American and Israeli universities with reinforced concrete US north of industries for outstanding researchers in the BIM area, Charles Eastman, Rafael Sacks Lee and Chang. Therefore, the development of this study was used as the science research strategy design, based method for BOB. The research development process took place in four stages: elucidation phase, design phase, validation phase and translation. At the end of work were generated diagrams, applicable in any BIM platform. The diagrams describe the process automation of masonry pagination